2012
DOI: 10.1097/iae.0b013e3182180087
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Endophthalmitis

Abstract: Posttraumatic endophthalmitis is more likely among patients with open-globe injury that are needle related and among those who have intraocular foreign bodies, traumatic lens rupture, smaller wounds, or wounds exclusively in the cornea. Lower ocular trauma scores in this group of patients with penetrating trauma indicated a greater risk of poor visual prognosis. Therefore, it is suggested that necessary measures and immediate treatment be undertaken in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
4
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
8
35
4
4
Order By: Relevance
“…In China, a total of 4795 OGIs were studied with a PTE incidence of 11.91%—eviscerated cases were excluded and the authors do not mention the routine use of antibiotic prophylaxis 22. In Iran, 117 cases of PTE out of 2340 OGIs were reported (an incidence of 5.1%) when patients were given intravenous antibiotics (cefazolin and gentamicin) for a period of 3 days 23. In a review of 558 patients with OGI from the USA,3 an incidence of 0.9% was found when intravenous vancomycin and ceftazidime prophylaxis was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, a total of 4795 OGIs were studied with a PTE incidence of 11.91%—eviscerated cases were excluded and the authors do not mention the routine use of antibiotic prophylaxis 22. In Iran, 117 cases of PTE out of 2340 OGIs were reported (an incidence of 5.1%) when patients were given intravenous antibiotics (cefazolin and gentamicin) for a period of 3 days 23. In a review of 558 patients with OGI from the USA,3 an incidence of 0.9% was found when intravenous vancomycin and ceftazidime prophylaxis was used.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the prevalence of culture-negative cases of PTE range from 17% to 42% 19 21 24. Several authors have emphasised the importance of using a clinical diagnosis of endophthalmitis and thus have included culture-negative cases in their studies 19 21 23…”
Section: Discussionmentioning
confidence: 99%
“…Instant wound closure eliminates the risk of endophthalmitis [7] if contamination has not already occurred, and also that of an expulsive hemorrhage; additionally, it is helpful in case of legal action against the surgeon. …”
Section: Open-globe Traumamentioning
confidence: 99%
“…These 4 cases gave an incidence of 11.1%. This is much higher than was published in an Iranian study that showed an incidence of 5.1% [18]. …”
Section: Discussionmentioning
confidence: 54%